Eucalyptus citriodora, E. phaeotricha and E. propinqua seeds subjected to classification by sieves - Barbosa, Ana Sara Vieira [UNESP]; Jeromini, Tatiane Sanches; da Silva, Givanildo Zildo; Martins, Cibele Chalita (My University, 2022)
Seeds’ qualities are influenced by several factors such as the density and size of seeds. The aim of this study was to evaluate the physical and physiological quality of Corymbia citriodora, E. phaeotricha and E. propinqua seeds that were subjected to classification by sieve. The seeds passed through sieves that retained the following sizes: C. citriodora (2.00; 1.68; 1.41; 1.19; 1.00 mm), E. phaeotricha (1.41; 1.19; 1.00; 0.84 mm) and E. propinqua (1.00; 0.84; 0.71; 0.59 e 0.50 mm). The tests of retention percentage, physical purity, germination, first count of germination, germination speed index and average germination time were performed. The design used was randomized with four replications and five treatments for C. citriodora and E. propinqua, and four treatments for E. phaeotricha, due to the number of sieves that retained seeds. The data were submitted to analysis of variance by the F test. When significant, the statistics related to the classification of seeds by sieves were compared using the Tukey test with 5% probability. The use of sieve classification is effective for the separation of seeds with high physical and physiological quality. C. citriodora with a seed size of 1.41 to 2.00 mm have maximum physical and physiological quality and can be pelleted. For E. phaeotricha and E. propinqua, seeds with a size of 1.19 to 1.41 mm and 0.84 to 1.00 mm, respectively, have the highest physical and physiological quality.
Sementes de Eucalyptus citriodora, E. phaeotricha e E. Propínqua submetidas a classificação por peneiras
Keywords: Germination; Myrtaceae; purity; seed size